Mengembangkan Aspek Sosial Anak Usia Dini Dengan Metode Permainan - Ana Isnainiyah; Maulidatul Afifatur; Ramadha Tsulatsi Hajar (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study presents the improvement of early childhood development through the game method. This aims to determine the application of the game method in early childhood and what efforts are used to improve the social development of early childhood. Games are physical activities in the form of small groups that allow collaboration between students. There are various kind of games that are applied to early childhood effectively so that they can optimize the social development of early childhood both at school and the surrounding and environtment. Analysis of the data used by observation, interviews and documentation. Sources of data from this study include the community, teachers, and children. Based on the results of the study, it can be interpreted that applying the game method to early childhood in social development by getting used to grouping children randomly can increase cooperation between students so that children’s ability to socialize with friends, teachers and surrounding environment also increases.